X-men. First class [videorecording (DVD)] - Vaughn, Matthew, 1971-; Vaughn, Matthew, 1971-; McAvoy, James, 1979-; Byrne, Rose; Hoult, Nicholas, 1989-; Lawrence, Jennifer, 1990-; Flemyng, Jason; Gathegi, Edi; Bacon, Kevin, 1958-; Fassbender, Michael, 1977-; Jones, January, 1978-; Platt, Oliver (Twentieth Century Fox Home Entertainment, 2011)
Before Charles Xavier and Erik Lensherr took the names Professor X and Magneto, they were two young men discovering their superhuman powers for the first time, working together in a desperate attempt to stop the Hellfire Club and a global nuclear war.